2018
DOI: 10.1007/s11695-018-3250-8
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Findings in Morbid Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy: Does H. pylori Infection Effective on Pathological Changes?

Abstract: The study included 114 women (70.8%) and 47 men (29.2%). The mean age of the patients was 36.82 ± 10.41 years, and the mean BMI was 46.05 ± 3.76 kg/m. H. pylori infection was detected in 103 (64%), chronic gastritis in 156, chronic active gastritis in 47, intestinal metaplasia in eight, and atrophy in seven patients. The rate of H. pylori-associated chronic gastritis was 64%, that of chronic active gastritis was 24.2%, that of lymphoid aggregation was 62.2%, and that of intestinal metaplasia and atrophy was 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In the light of, the higher percentage of a large range of upper GI tract disorders in obese patients in our study that were confirmed with similar studies done on histopathological specimens of LSG [30][31][32]. We recommend performing a routine preoperative endoscopic evaluation for patients before bariatric surgery even if they are asymptomatic, which may help in the diagnosis of GI pathologies affecting both the surgery and the bariatric follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…In the light of, the higher percentage of a large range of upper GI tract disorders in obese patients in our study that were confirmed with similar studies done on histopathological specimens of LSG [30][31][32]. We recommend performing a routine preoperative endoscopic evaluation for patients before bariatric surgery even if they are asymptomatic, which may help in the diagnosis of GI pathologies affecting both the surgery and the bariatric follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Although these findings may cause the surgeon to change the way of treatment in the postoperative period, most of the reported diagnoses do not require further clinical follow-up (14). In our series, there was no patient requiring treatment change in the postoperative period.…”
Section: Discussionmentioning
confidence: 56%
“…An explanation for these discrepancies in pathological results found across the published studies may be represented by the different classifications of abnormal histopathological findings that were used in different countries. For instance, Oner et al [20] used the same classification as ours, but they found chronic gastritis in 96.9% of the cases, as the most common abnormal finding, followed by lymphoid aggregates and active chronic gastritis in 87.2% and 29.2%, respectively. In another study by Adalı et al [21], they also used the same classification as ours, but besides that, they had one more item, namely "lymphoid follicles", which was encountered in 59.5% of the cases.…”
Section: Discussionmentioning
confidence: 62%